Análise e desenvolvimento de um modelo de decisão em ambiente de produção com gestão de múltiplos projetos - Guarienti, Édio Patric (2013)
This dissertation aims to develop a decision model for sequencing production activities to optimize the delivery time of projects. The survey classify him as applied and descriptive with qualitative and quantitative approach, having how the procedure the single case study. To develop the decision model was used the process flow map to identify the critical control points and determining the evaluation and priorization criteria of project activities for each subprocess. After, it were measured all evaluation criteria identified by mathematical formulas and it was subsequently drafted a simulation tool for priorization and decision on multiple projects to sequence the production activities. The base-building of simulation tool was the Microsoft Excel® software application. The tool was used in a lower hierarchical level to identify the projects to be executed with better success, aiming to maximize revenue. The model was tested in a electromechanical industry located in northwest of Rio Grande do Sul, where it was randomly selected six projects with engineering and custom manufacturing(ETO and MTO) among twenty projects that are executed in average per month. As a result, it was obtained the projects analyzed according to criteria adopted, which should be prioritized in production without compromising delivery time to the customer and the earnings of the company. Therefore, one can conclude that the tool can assist in prioritization of project execution type (ETO and MTO).